Transient Ischaemic Attack (TIA) Knowledge in General Practice: a cross-sectional study of Western Adelaide general practitioners - Leung, Elaine Stephanie (BioMed Central, 2012)
BACKGROUND: With evidence to support early assessment and management of TIAs, the role of the general practitioner (GP) needs to be considered in developing a TIA service in Western Adelaide. We thus aimed to determine GP knowledge of TIA assessment and management and identify perceived barriers, in order to tailor subsequent GP education and engage primary care in the co-ordinated care of TIA patients. FINDINGS: A self-administered questionnaire was mailed to all GPs (n = 202) in the Adelaide Western General Practice Network. Response frequencies were calculated for all variables, and associations examined by univariate analysis. 32 GPs responded. All respondents correctly identified early risk of stroke following a TIA. Difficulty accessing neurological expertise was identified as a barrier (40.6 %), as was a lack of GP knowledge (18.8 %). Areas for improvement included access to neurologists (36.7 %), relevant guidelines and education (43.3 %). CONCLUSIONS: Diagnosis of TIA is difficult and this study highlights the need for further education and practical guidelines for GPs. With this training, GPs could be better equipped to assess and manage TIAs effectively in the community in consultation with stroke physicians.